Failure behaviour of the single lap joints of angle-plied composites under three point bending tests. Issue 5 (3rd March 2020) - Kadioglu, Ferhat; Demiral, Murat
Abstract: In this paper, the response of adhesively-bonded single lap joints (SLJs) with angle-plied composite adherends subjected to flexural loading was investigated. The experiments were carried out for the adherends, glass reinforced polymer matrix, with three kinds of stacking sequence. A three-dimensional finite element (FE) model was developed using ABAQUS/Explicit. The three dimensional Hashin failure criterion with an appropriate damage evolution law was used to characterize the damage inside a ply. Cohesive zone elements were used to model the damage in the adhesive layer (AF163-2K) and the interply failure, that is, the delamination. The developed numerical model was verified with the performed experiments. The SLJs of [±20]5s and [±45]5s failed due to failure in the adhesive layer and the delamination between the plies, whereas that of [±10]5s failed mainly due to the former failure. The intralaminar damage was not noticed for any case. The influence of the fiber angle of plies in the adherends, adherend thickness, overlap length, and the thickness of adhesive layer on the damage in the adhesive layer and the delamination were investigated in terms of the competition between these two failures and activation of different failure modes in each thoroughly.